1990
DOI: 10.1128/jvi.64.6.3063-3068.1990
|View full text |Cite
|
Sign up to set email alerts
|

Tandemly repeated hexamer sequences within the beta interferon promoter can function as an inducible regulatory element in activation by the adenovirus E1B 19-kilodalton protein

Abstract: The expression of the human beta interferon (IFN-,) gene was activated by the adenovirus ElB-19K protein. The sequence within the IFN-j8 promoter which is related to the activation was analyzed by chloramphenicol acetyltransferase (CAT) assay. The repeated hexamer units, present within the region between-109 and-65 relative to the cap site, were required for the activation of the IFN-13 gene by the ElB-19K protein. The (AAGTGA)8 region, as a typical hexamer of the consensus sequences, was tested for function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…5A). This result corroborates and extends the previous findings that ElB-19K is an activator of several RNA Pol II genes in transient transfection experiments and counteracts the inhibitory effect of ElA on RNA Pol II transcription (20,39,49,66) (Fig. 5C).…”
Section: Discussionsupporting
confidence: 92%
“…5A). This result corroborates and extends the previous findings that ElB-19K is an activator of several RNA Pol II genes in transient transfection experiments and counteracts the inhibitory effect of ElA on RNA Pol II transcription (20,39,49,66) (Fig. 5C).…”
Section: Discussionsupporting
confidence: 92%
“…gested that the 19K protein may act directly or indirectly to repress ElA-dependent early gene transcription. However, in plasmid transfection experiments, it was concluded that the ElB-19K protein stimulates expression from Ad and certain cellular promoters (26,45,54,73,91). The activation may be due, at least in part, to a relief from ElA-mediated enhancer repression (91).…”
Section: Fig 2 An Adenovirus Early Protein Protects Hel-299 Cellsmentioning
confidence: 99%
“…Increased gene expression by the ElB-19K protein has also been detected in ElA-negative Ads (26, 73, 85). However, a later report suggested that the increased transcription by the ElB-19K protein of transfected plasmids was indirect and resulted from stabilization by the ElB-19K protein of the transfected plasmid DNA (27), although this was not observed with the Adl2 ElB-19K protein (54). Therefore, the role of the ElB-19K protein in gene regulation is unclear at present.…”
Section: Fig 2 An Adenovirus Early Protein Protects Hel-299 Cellsmentioning
confidence: 99%
“…3Y1 cells were transfected with each of pNeol2ElA, pNeo3E(12S) EMA, pNeo13SE1A, pNeoPv2ElA, pNeoRsa2ElA, pNeo SE1A, pNeo5-12E1A, pNeol2-5E1A, and pNeoElB. 3Y1 cells were also cotransfected with pSV2Neo and pMT-1 (SV40 T), SRp53, pRmyc27, pFBJ-2 (v-fos), and pMK-fos DNAs by the calcium phosphate technique described previously (32,33). At 40 h after transfection, the cells were trypsinized and replated at a 1:3 dilution.…”
Section: Rsv3y1-k-mix)mentioning
confidence: 99%
“…Assay for CAT activity. The assay for chloramphenicol acetyltransferase (CAT) activity was carried out as described previously (4,32,34). At 48 h after transfection with 0.1, 0.03, and 0.01, ,ug of LTR-CAT DNA, the cells (4-cm plate) were scraped off for the CAT assay.…”
Section: Rsv3y1-k-mix)mentioning
confidence: 99%